Instruments for Supporting Implementation of Sustainable Development Goals for Construction Sector – Case of Poland - Szopińska, Kinga; Ramczyk, Marek (Geomatics and Environmental Engineering, 2024)
Currently, three billion people face dangerous levels of air pollution and rely on non-renewable energy sources for cooking and heating. Due to its environmental impact, the construction sector is a particularly important area for implementing sustainable development policies. On July 10, 2023, the UN published The Sustainable Development Goals Report 2023 (SDGs). In accordance with the provisions of Goal 7 (which was discussed in the above document), the international community should increase its share of renewable energy sources in the global energy mix and promote investment in clean energy technologies by 2030. Achieving this goal necessitates the introduction of support mechanisms to enhance the energy efficiency of residential buildings. Hence, this study aims to showcase the legal and financial tools that aid the growth of energy-efficient construction in Poland, to compare the renovation costs of an existing residential building in order to meet energy-efficiency standards, and to detail the financial support that is available for planned thermal-modernization efforts.